The role of the inner radiation belt dynamic in the generation of auroral-type sporadic E-layers over south American magnetic anomaly - Da Silva, L. A.; Shi, J; Resende, L. C. A.; Agapitov, O. V.; Alves, L. R.; Batista, I. S.; Arras, C.; Vieira, L. E.; Deggeroni, V.; Marchezi, J. P.; Wang, C.; Moro, J.; et al. (Frontiers in Astronomy and Space Sciences, 2022)
The dynamics of the electron population in the Earth’s radiation belts affect the upper atmosphere's ionization level through the low-energy Electron Precipitation (EP). The impact of low-energy EP on the high-latitude ionosphere has been well explained since the 1960's decade. Conversely, it is still not well understood for the region of the South American Magnetic Anomaly (SAMA). In this study, we present the results of analysis of the strong geomagnetic storm associated with the Interplanetary Coronal Mass Ejection (May 27-28, 2017). The atypical auroral sporadic E layers (Esa) over SAMA are observed in concomitance with the hiss and magnetosonic wave activities in the inner radiation belt. The wave-particle interaction effects have been estimated, and the dynamic mechanisms that caused the low-energy EP over SAMA were investigated. We suggested that the enhancement in pitch angle scattering driven by hiss waves result in the low-energy EP (≥ 10 keV) into the atmosphere over SAMA. The impact of these precipitations on the ionization rate at the altitude range from 100 km to 120 km can generate the Esa layer in this peculiar region. In contrast, we suggested that the low-energy EP (≤ 1 keV) causes the maximum ionization rate close to 150 km altitude, contributing to the Esa layer occurrence in these altitudes.